2015
DOI: 10.1039/c5nr01031d
|View full text |Cite
|
Sign up to set email alerts
|

Facile production of stable silicon nanoparticles: laser chemistry coupled to in situ stabilization via room temperature hydrosilylation

Abstract: Stable, alkyl-terminated, light-emitting silicon nanoparticles have been synthesized in a continuous process by laser pyrolysis of a liquid trialkyl-silane precursor selected as a safer alternative to gas silane (SiH 4 ). Stabilization was achieved by in situ reaction using a liquid collection system instead of the usual solid state filtration. The alkene contained in the collection liquid (1-dodecene) reacted with the newly formed silicon nanoparticles in an unusual room-temperature hydrosilylation process. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…The analysis of C 1s and O 1s signals confirmed the presence of Si–CH x , C–O and C–OH surface groups (Table S3 † ). 47 , 52 , 53…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of C 1s and O 1s signals confirmed the presence of Si–CH x , C–O and C–OH surface groups (Table S3 † ). 47 , 52 , 53…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of Pt x Co y /C composite nanoparticles with different compositions has been carried out by laser pyrolysis in a continuous flow reactor described elsewhere (Martínez et al, 2012 ; Malumbres et al, 2013 , 2015 ). The starting solution employed for the synthesis of Pt x Co y /C was prepared by dissolving Pt(acac) 2 (47 mg, 0.12 mmol) and the corresponding amount of Co(acac) 3 [11 mg (0.04 mmol) or 30 mg (0.12 mmol)] in toluene, to get a molar ratio Pt:Co = 3 or Pt:Co = 1.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we propose a simple one-pot synthesis method for alloying nanoparticles containing C shells, based on laser pyrolysis processing. Previous studies in our group have shown that this technique could be used to successfully synthesize a variety of nanoparticles with extremely high purity (Martínez et al, 2012 ; Malumbres et al, 2015 ). Although most of the research in this area is limited to metal precursors which are gases or liquid having sufficient vapor pressure at moderate temperature, which restricts its application to certain elements or makes necessary to synthesize specific organometallic precursors or even use highly flammable and toxic precursors as it is the case of silane for the synthesis of Si nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these methods display limited availability of control in stoichiometry requirements, making them very restricted processes for the synthesis of doped CNDs. Among the laser synthesis methods, laser pyrolysis represents an elegant alternative for the one-pot synthesis of a wide variety of carbonaceous materials, including amorphous carbon materials, fullerenes, carbon black, carbides or even graphene powders In the process of CO2 laser pyrolysis [45,[56][57][58][59][60] the reaction proceeds in-between the laser beam and the molecular flow of gaseous/vapors phase reactants. The resultant condensable products are generated at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have tested these CNDs as sensitizers to extend the photocatalytic response of titania beyond the UV range [21, 25-31, 35, 41] in the photodegradation of an organic dye [63][64][65]. Volatile organic solvents (toluene and pyridine) were selected as carbon precursors, whereas the generated nanoparticles after laser irradiation were collected in a liquid media to prevent coalescence events [45,56,57]. With this selection we aimed at evaluating the potential N-doping effects caused by the subtle modification of the chemical composition of the organic precursors (by introducing an N heteroatom).…”
Section: Introductionmentioning
confidence: 99%